Arabidopsis Fructokinases Are Important for Seed Oil Accumulation and Vascular Development - Stein, Ofer; Avin-Wittenberg, Tamar; Krahnert, Ina; Zemach, Hanita; Bogol, Vlada; Daron, Oksana; Aloni, Roni; Fernie, Alisdair R.; Granot, David (Frontiers in Plant Science, 2017)
Sucrose (a disaccharide made of glucose and fructose) is the primary carbon source transported to sink organs in many plants. Since fructose accounts for half of the hexoses used for metabolism in sink tissues, plant fructokinases (FRKs), the main fructose-phosphorylating enzymes, are likely to play a central role in plant development. However, to date, their specific functions have been the subject of only limited study. The Arabidopsis genome contains seven genes encoding six cytosolic FRKs and a single plastidic FRK. T-DNA knockout mutants for five of the seven FRKs were identified and used in this study. Single knockouts of the FRK mutants did not exhibit any unusual phenotype. Double-mutants of AtFRK6 (plastidic) and AtFRK7 showed normal growth in soil, but yielded dark, distorted seeds. The seed distortion could be complemented by expression of the well-characterized tomato SlFRK1, confirming that a lack of FRK activity was the primary cause of the seed phenotype. Seeds of the double-mutant germinated, but failed to establish on 1/2 MS plates. Seed establishment was made possible by the addition of glucose or sucrose, indicating reduced seed storage reserves. Metabolic profiling of the double-mutant seeds revealed decreased TCA cycle metabolites and reduced fatty acid metabolism. Examination of the mutant embryo cells revealed smaller oil bodies, the primary storage reserve in Arabidopsis seeds. Quadruple and penta FRK mutants showed growth inhibition and leaf wilting. Anatomical analysis revealed smaller trachea elements and smaller xylem area, accompanied by necrosis around the cambium and the phloem. These results demonstrate overlapping and complementary roles of the plastidic AtFRK6 and the cytosolic AtFRK7 in seed storage accumulation, and the importance of AtFRKs for vascular development.